Waterproof and damping rubber composite material for tunnel and preparation method of waterproof and damping rubber composite material
By using rubber composite materials composed of wear-resistant layer, waterproof layer, shock-absorbing energy-absorbing layer and bonding layer in tunnel engineering, the shortcomings of rubber waterproof plates in the prior art in terms of scratch-resistant wear and buffering performance are solved. , achieve effective waterproofing and shock absorption performance in complex tunnel environments.
Patent Information
- Application Number
- CN202411682483.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-02-14
AI Technical Summary
The film structure of existing rubber waterproof boards for tunnel engineering is insufficient in terms of scratch resistance and wear resistance, and cannot adapt to complex tunnel environments. At the same time, the buffering performance is poor, making it difficult to effectively reduce earthquake hazards.
Using rubber composite material composed of wear-resistant layer, waterproof layer, shock-absorbing energy-absorbing layer and bonding layer, the shock-absorbing energy-absorbing layer absorbs seismic energy through multiple trapezoidal rib structures, and generates heat through the movement of macromolecules to convert energy. It is deformation energy and heat energy.
It achieves effective waterproofing and shock absorption performance in the tunnel environment. The rib structure absorbs energy and generates heat during earthquakes, enhancing the energy-consuming and shock absorption performance of the material, and at the same time, the bonding layer is easy to install and use.
Smart Images

Figure CN119432245A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of rubber waterproof products, and in particular relates to a rubber composite material for tunnel waterproofing and shock absorption and a preparation method thereof. Background Art
[0002] Rubber products have been widely used in the field of tunnel engineering. Specifically, rubber materials are attached to the rock wall of the tunnel or between the primary lining and the secondary lining. The rubber materials can prevent groundwater from seeping into the tunnel and ensure the safety of tunnel operation. At the same time, when an earthquake occurs, the rubber materials can dissipate the seismic energy exerted on the tunnel structure as heat energy or other forms of energy, thereby reducing the damage caused by structural earthquakes.
[0003] Existing rubber products in the field of tunnel engineering are usually film structures, which only play a waterproof role, and have insufficient scratch and wear resistance. They cannot adapt to the complex environment of tunnels with uneven surfaces and edges. Therefore, it is usually necessary to lay geotextiles on the primary lining as a cushion layer, and the construction process is complicated. At the same time, the buffering performance of the film structure is poor, and it is difficult to effectively reduce the earthquake hazards when an earthquake occurs.
[0004] The existing rubber waterproofing sheets for tunnel engineering are usually fixed on the tunnel surface by hot-melt method. In order to prevent the waterproofing sheets from falling off, hot-melt washers are usually fixed on the tunnel surface and heated by hot-melt equipment to firmly bond the hot-melt washers to the waterproofing sheets. Summary of the invention
[0005] The purpose of the present invention is to provide a rubber composite material for tunnel waterproofing and shock absorption and a preparation method thereof. The composite material has firm connections between layers and can meet the two major requirements of tunnel waterproofing and shock absorption. At the same time, the bottom has an adhesive layer, which is convenient for installation and use in a tunnel environment.
[0006] The present invention adopts the following technical scheme: a rubber composite material for tunnel waterproofing and shock absorption, comprising, from top to bottom, a wear-resistant layer, a waterproof layer, a shock-absorbing and energy-absorbing layer and a bonding layer stacked together in sequence;
[0007] The bonding layer is made of a composite bonding agent;
[0008] The shock-absorbing and energy-absorbing layer includes a bottom plate on which a plurality of ribs are arranged. Each rib is arranged along a front-to-back direction, and a plurality of ribs are arranged at intervals along a left-to-right direction. Each rib is wide at the bottom and narrow at the top, and its longitudinal section is a trapezoid that is wide at the bottom and narrow at the top. The ribs are used to reduce the energy transmitted to the tunnel by an earthquake.
[0009] Furthermore, the bottom plate has a thickness of 10 to 20 mm, a rib height of 40 to 50 mm, an upper width of the rib of 30 to 40 cm, a lower width of 50 cm, and a spacing between two adjacent ribs of 5 to 10 mm.
[0010] Furthermore, the composite adhesive is prepared from the following raw materials in parts by weight: 100 parts of butyl rubber, 30-50 parts of calcium carbonate powder, 3-7 parts of cyclohexane oil, 10-30 parts of polyisobutylene, 5-10 parts of APAO, and 2-6 parts of aluminum oxide powder.
[0011] Furthermore, the raw materials of the shock-absorbing and energy-absorbing layer are made of the following raw materials in parts by weight: 100 parts of natural rubber, 50 parts of carbon black, 2 parts of microcrystalline wax, 1 part of sulfur, 1-3 parts of antioxidant RD, 0.5-1.5 parts of antioxidant 4020, 0.8-1.2 parts of accelerator CZ, and 0.5-0.8 parts of accelerator DM.
[0012] Furthermore, the raw materials of the waterproof layer are made of the following raw materials in parts by weight: 30-40 parts of linear low-density polyethylene, 30-40 parts of medium-density polyethylene, 30-40 parts of ethylene-vinyl acetate copolymer, and 2-5 parts of antioxidant 4020.
[0013] Furthermore, the raw materials of the wear-resistant layer are made of the following raw materials in parts by weight: 70 parts of natural rubber, 30 parts of butadiene rubber, 20-50 parts of carbon black, 5-10 parts of white carbon black, 10 parts of aromatic oil, 1-3 parts of antioxidant 4020, 2-4 parts of sulfur, and 1-2 parts of aluminum oxide.
[0014] Further, the thickness of the bonding layer is 1 mm;
[0015] The thickness of the shock-absorbing and energy-absorbing layer is 60 mm;
[0016] The thickness of the waterproof layer is 1.2mm;
[0017] The thickness of the wear-resistant layer is 0.5 mm.
[0018] The present invention also discloses a method for preparing the above-mentioned rubber composite material for tunnel waterproofing and shock absorption, comprising the following steps:
[0019] Step 1, weigh the above raw materials;
[0020] Step 2: Put butyl rubber, calcium carbonate powder, cyclohexane oil, polyisobutylene, APAO and alumina powder into an open mill for mixing at a temperature of 40-85°C and a drilling speed of 30-60rpm, put the mixed rubber into an extruder at a temperature of 100-125°C, extrude into a continuous sheet, and obtain a bonding layer;
[0021] Put natural rubber, carbon black, microcrystalline wax, sulfur, antioxidant RD, antioxidant 4020, accelerator CZ and accelerator DM into an open mill for mixing at a temperature of 40-85°C and a drilling speed of 30-60rpm, put the mixed rubber material into an extruder at a temperature of 90-120°C, extrude the rubber material into strips, and then cut it into blocks, heat the block rubber material to 50-70°C and place it in a molding mold, and form it through hydraulic pressure to obtain a shock-absorbing energy-absorbing layer;
[0022] Put linear low-density polyethylene, medium-density polyethylene, ethylene-vinyl acetate copolymer and antioxidant 4020 into an open mill for mixing at a temperature of 40-85°C and a drilling speed of 30-60rpm, put the mixed rubber material into an extruder at a temperature of 100-125°C, extrude it into a continuous sheet, and obtain a waterproof layer;
[0023] Put natural rubber, butadiene rubber, carbon black, white carbon black, aromatic oil, antioxidant 4020, sulfur and alumina into an open mill for mixing at a temperature of 40-85°C and a drilling speed of 30-60rpm, put the mixed rubber into an extruder at a temperature of 100-125°C, extrude into a continuous sheet, and obtain a wear-resistant layer;
[0024] Step 3: stack the wear-resistant layer, waterproof layer, shock-absorbing layer and bonding layer from top to bottom, heat to 100-120° C., perform hot pressing for 10-20 seconds, and cool to obtain the product.
[0025] The beneficial effects of the present invention are: 1. By setting a plurality of ribs, the ribs absorb seismic energy and deform after an earthquake, and at the same time, the internal friction of the movement of internal macromolecules generates heat, converting seismic energy into deformation energy and thermal energy. 2. When the seismic energy is small, the deformation of the ribs is not restricted, and at this time the rib stiffness is small, and the shock absorption capacity is stronger; when the input seismic wave energy is large, the up and down forces squeeze the ribs downward, and the ribs deform downward, and the lower parts of adjacent ribs contact each other upward and left and right, and at the same time, the lateral deformation of each rib is restricted, the rib stiffness becomes larger, the supporting capacity is stronger, and a strong support is formed. 3. A bonding layer is set at the bottom to facilitate installation and use in a tunnel environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 A schematic diagram of a rubber composite material for waterproofing and shock absorption in tunnels;
[0027] Figure 2 is a schematic diagram of the shock-absorbing and energy-absorbing layer;
[0028] Among them: 101. bonding layer; 102. shock-absorbing and energy-absorbing layer; 103. waterproof layer; 104. wear-resistant layer; 1021. bottom plate; 1022. ribs. DETAILED DESCRIPTION
[0029] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0030] The present invention discloses a rubber composite material for tunnel waterproofing and shock absorption, such as Figure 1 As shown, from top to bottom, it includes a wear-resistant layer 104, a waterproof layer 103, a shock-absorbing layer 102 and a bonding layer 101 stacked together in sequence; the wear-resistant layer 104 is about 0.5 mm thick, and the waterproof layer 103 is about 1.2 mm thick. The shock-absorbing layer 102 is 60 mm thick. The bonding layer 101 is made of a composite adhesive; the bonding layer 101 is about 1 mm thick.
[0031] like Figure 2 As shown, the shock-absorbing and energy-absorbing layer 102 includes a base plate 1021, on which a plurality of ribs 1022 are arranged, each rib 1022 is arranged along the front-to-back direction, and a plurality of ribs 1022 are arranged at intervals along the left-to-right direction, each rib 1022 is wide at the bottom and narrow at the top, and a longitudinal section thereof is a trapezoid that is wide at the bottom and narrow at the top; the ribs 1022 are used to buffer seismic energy, and can effectively prevent the occurrence of interlayer shear failure under the action of an earthquake, thereby enhancing the energy dissipation and shock-absorbing performance of the shock-absorbing and energy-absorbing layer 102.
[0032] The specific functions of the above-mentioned ribs 1022 are as follows: 1. Absorb and transform earthquake energy: after an earthquake, the ribs absorb earthquake energy and deform, and at the same time, the internal friction of the internal macromolecules generates heat, converting earthquake energy into deformation energy and heat energy. 2. It has both shock absorption and support functions. When the input seismic wave energy is small, the rib deformation is not restricted. At this time, the rib stiffness is small and the shock absorption capacity is stronger; when the input seismic wave energy is large, the up and down forces squeeze the ribs 1022 downward, and the ribs 1022 deform downward. The lower parts of adjacent ribs 1022 contact each other upward and left and right, and at the same time, the ribs 1022 are restricted from further deformation in the left and right directions. The ribs 1022 become more rigid and have stronger support capacity.
[0033] The thickness of the bottom plate 1021 of the shock-absorbing layer 102 is 10-20 mm, the height of the ribs 1022 is 40-50 mm, the upper width of the ribs 1022 is 30-40 cm, the lower width is 50 cm, and the interval between two adjacent ribs 1022 is 5-10 mm.
[0034] The composite adhesive is prepared from the following raw materials in parts by weight: 100 parts of butyl rubber, 30-50 parts of calcium carbonate powder, 3-7 parts of naphthenic oil, 10-30 parts of polyisobutylene, 5-10 parts of APAO, and 2-6 parts of aluminum oxide powder. The calcium carbonate powder is nano-active calcium carbonate powder with an average particle size of 10-100nm and a purity of more than 98%. It is washed with water before use, and stearic acid and lignin are added to activate the powder surface, and then dried.
[0035] The average particle size of the alumina powder is 30-100nm, the purity is greater than 98%, and the density is 3.8-4.2g / cm3. Before use, it is washed with water, and stearic acid and lignin are added to activate the powder surface, and then dried.
[0036] The raw materials of the shock-absorbing and energy-absorbing layer 102 are made of the following raw materials in parts by weight: 100 parts of natural rubber, 50 parts of carbon black, 2 parts of microcrystalline wax, 1 part of sulfur, 1-3 parts of antioxidant RD, 0.5-1.5 parts of antioxidant 4020, 0.8-1.2 parts of accelerator CZ, and 0.5-0.8 parts of accelerator DM.
[0037] The carbon black is wear-resistant carbon black for rubber, with an average particle size of 40-50nm, a particle crushing strength greater than 20MPa, and a tinting strength of 97-109%. The sulfur is S-80 granular sulfur with a density of 1.64g / cm3. More preferably, EPDM rubber can be used as a carrier, and stearic acid can be added as a surfactant dispersant. The main component of white carbon black is silicon dioxide powder, with a silicon dioxide content of not less than 98% and a density of 2.6-2.8g / mm 3 .
[0038] The raw materials of the waterproof layer 103 are made of the following raw materials in parts by weight: 30-40 parts of linear low-density polyethylene, 30-40 parts of medium-density polyethylene, 30-40 parts of ethylene-vinyl acetate copolymer, and 40202-5 parts of antioxidant.
[0039] The raw materials of the wear-resistant layer 104 are made of the following raw materials in parts by weight: 70 parts of natural rubber, 30 parts of butadiene rubber, 20-50 parts of carbon black, 5-10 parts of white carbon black, 10 parts of aromatic oil, 1-3 parts of antioxidant 4020, 2-4 parts of sulfur, and 1-2 parts of aluminum oxide.
[0040] The composite adhesive is prepared from the following raw materials in parts by weight: 100 parts of butyl rubber, 30-50 parts of calcium carbonate powder, 3-7 parts of cyclohexane oil, 10-30 parts of polyisobutylene, 5-10 parts of APAO and 2-6 parts of aluminum oxide powder.
[0041] The raw materials of the shock-absorbing and energy-absorbing layer 102 are made of the following raw materials in parts by weight: 100 parts of natural rubber, 50 parts of carbon black, 2 parts of microcrystalline wax, 1 part of sulfur, 1-3 parts of antioxidant RD, 0.5-1.5 parts of antioxidant 4020, 0.8-1.2 parts of accelerator CZ, and 0.5-0.8 parts of accelerator DM.
[0042] The raw materials of the waterproof layer 103 are made of the following raw materials in parts by weight: 30-40 parts of linear low-density polyethylene, 30-40 parts of medium-density polyethylene, 30-40 parts of ethylene-vinyl acetate copolymer, and 40202-5 parts of antioxidant.
[0043] The raw materials of the wear-resistant layer 104 are made of the following raw materials in parts by weight: 70 parts of natural rubber, 30 parts of butadiene rubber, 20-50 parts of carbon black, 5-10 parts of white carbon black, 10 parts of aromatic oil, 1-3 parts of antioxidant 4020, 2-4 parts of sulfur, and 1-2 parts of aluminum oxide.
[0044] The thickness of the adhesive layer 101 is 1 mm;
[0045] The thickness of the shock-absorbing and energy-absorbing layer 102 is 60 mm;
[0046] The thickness of the waterproof layer 103 is 1.2 mm;
[0047] The thickness of the wear-resistant layer 104 is 0.5 mm.
[0048] The present invention also discloses a method for preparing the above-mentioned rubber composite material for tunnel waterproofing and shock absorption, comprising the following steps:
[0049] Step 1, weigh the above raw materials;
[0050] Step 2: Put butyl rubber, calcium carbonate powder, cyclohexane oil, polyisobutylene, APAO and alumina powder into an open mill for mixing at a temperature of 40-85° C. and a drilling speed of 30-60 rpm, put the mixed rubber into an extruder at a temperature of 100-125° C., extrude into a continuous sheet, and obtain a bonding layer 101;
[0051] Natural rubber, carbon black, microcrystalline wax, sulfur, antioxidant RD, antioxidant 4020, accelerator CZ, and accelerator DM are put into an open mill for mixing at a temperature of 40-85° C. and a drilling speed of 30-60 rpm. The uniformly mixed rubber material is put into an extruder at a temperature of 90-120° C. The rubber material is extruded into strips and then cut into blocks. The block rubber material is heated to 50-70° C. and placed in a molding mold, and hydraulic pressure molding is performed to obtain a shock-absorbing and energy-absorbing layer 102.
[0052] Put linear low-density polyethylene, medium-density polyethylene, ethylene-vinyl acetate copolymer and antioxidant 4020 into an open mill for mixing at a temperature of 40-85° C. and a drilling speed of 30-60 rpm, put the mixed rubber material into an extruder at a temperature of 100-125° C., extrude it into a continuous sheet, and obtain a waterproof layer 101;
[0053] Natural rubber, butadiene rubber, carbon black, white carbon black, aromatic oil, antioxidant 4020, sulfur and alumina are put into an open mill for mixing at a temperature of 40-85° C. and a drilling speed of 30-60 rpm. The mixed rubber is put into an extruder at a temperature of 100-125° C. and extruded into a continuous sheet to obtain a wear-resistant layer 104.
[0054] Step 3: stack the wear-resistant layer 104, the waterproof layer 103, the shock-absorbing layer 102 and the bonding layer 101 from top to bottom, heat them to 100-120°C, heat-press them for 10-20s, perform hot-melt pressing to firmly bond the layers, and cool them down to obtain the product.
[0055] In order to verify the rubber composite material for tunnel waterproofing and shock absorption of the present invention, the following specific examples and comparative examples are given.
[0056] Example 1
[0057] The bonding layer 101 is made of a composite bonding agent, and the composite bonding agent is prepared from the following raw materials in parts by weight: 100 parts of butyl rubber, 50 parts of calcium carbonate powder, 3 parts of cyclohexane oil, 10 parts of polyisobutylene, 5 parts of APAO, and 2 parts of aluminum oxide powder.
[0058] The butyl rubber, calcium carbonate powder, cyclohexane oil, polyisobutylene, APAO and alumina powder are put into an open mill for mixing at a temperature of 70°C and a drilling speed of 50 rpm. The uniformly mixed rubber material is put into an extruder at a temperature of 110°C and extruded into a continuous sheet to obtain a bonding layer 101.
[0059] The raw materials of the shock-absorbing and energy-absorbing layer 102 are made of the following raw materials in parts by weight: 100 parts of natural rubber, 50 parts of carbon black, 2 parts of microcrystalline wax, 1 part of sulfur, 1 part of antioxidant RD, 0.5 parts of antioxidant 4020, 0.8 parts of accelerator CZ, and 0.5 parts of accelerator DM.
[0060] The above-mentioned natural rubber, carbon black, microcrystalline wax, sulfur, antioxidant RD, antioxidant 4020, accelerator CZ and accelerator DM are put into an open mill for mixing at a temperature of 70°C and a drilling speed of 50rpm. The uniformly mixed rubber material is put into an extruder at a temperature of 110°C, and the rubber material is extruded into strips, and then cut into blocks in batches using a rubber cutting machine. The block rubber material is heated to 65°C and placed in a molding mold, and hydraulic pressure molding is performed to obtain a shock-absorbing and energy-absorbing layer.
[0061] The thickness of the bottom plate 1021 is 10 mm, the height of the ribs 1022 is 50 mm, the width of the upper part of the ribs is 30 mm, the width of the lower part of the ribs is 50 mm, and the interval between two adjacent ribs 1022 is 10 mm.
[0062] The raw materials of the waterproof layer 103 are made of the following raw materials in parts by weight: 30 parts of linear low-density polyethylene, 30 parts of medium-density polyethylene, 30 parts of ethylene-vinyl acetate copolymer, and 2 parts of antioxidant 4020.
[0063] Linear low-density polyethylene, medium-density polyethylene, ethylene-vinyl acetate copolymer and antioxidant 4020 are put into an open mill for mixing at a temperature of 70°C and a drilling speed of 50 rpm. The evenly mixed rubber material is put into an extruder at a temperature of 110°C and extruded into a continuous sheet to obtain a waterproof layer 103.
[0064] The raw materials of the wear-resistant layer 104 are made of the following raw materials in parts by weight: 70 parts of natural rubber, 30 parts of butadiene rubber, 20 parts of carbon black, 5 parts of white carbon black, 10 parts of aromatic oil, 1 part of antioxidant 4020, 2 parts of sulfur, and 1 part of aluminum oxide.
[0065] Natural rubber, butadiene rubber, carbon black, white carbon black, aromatic oil, antioxidant 4020, sulfur and alumina are put into an open mill for mixing at a temperature of 70°C and a drilling speed of 50 rpm. The uniformly mixed rubber material is put into an extruder at a temperature of 110°C and extruded into a continuous sheet to obtain a wear-resistant layer 104.
[0066] Example 2
[0067] The bonding layer 101 is made of a composite bonding agent, and the composite bonding agent is prepared from the following raw materials in parts by weight: 100 parts of butyl rubber, 40 parts of calcium carbonate powder, 5 parts of cyclohexane oil, 20 parts of polyisobutylene, 8 parts of APAO, and 4 parts of aluminum oxide powder.
[0068] The butyl rubber, calcium carbonate powder, cyclohexane oil, polyisobutylene, APAO and alumina powder are put into an open mill for mixing at a temperature of 70°C and a drilling speed of 50 rpm. The uniformly mixed rubber material is put into an extruder at a temperature of 110°C and extruded into a continuous sheet to obtain a bonding layer 101.
[0069] The raw materials of the shock-absorbing and energy-absorbing layer 102 are made of the following raw materials in parts by weight: 100 parts of natural rubber, 50 parts of carbon black, 2 parts of microcrystalline wax, 1 part of sulfur, 2 parts of antioxidant RD, 1 part of antioxidant 4020, 1 part of accelerator CZ, and 0.7 parts of accelerator DM.
[0070] The above-mentioned natural rubber, carbon black, microcrystalline wax, sulfur, antioxidant RD, antioxidant 4020, accelerator CZ and accelerator DM are put into an open mill for mixing at a temperature of 70°C and a drilling speed of 50rpm. The uniformly mixed rubber material is put into an extruder at a temperature of 110°C, and the rubber material is extruded into strips, and then cut into blocks in batches using a rubber cutting machine. The block rubber material is heated to 65°C and placed in a molding mold, and hydraulic pressure molding is performed to obtain a shock-absorbing and energy-absorbing layer.
[0071] The thickness of the bottom plate 1021 is 10 mm, the height of the ribs 1022 is 50 mm, the width of the upper part of the ribs is 30 mm, the width of the lower part of the ribs is 50 mm, and the interval between two adjacent ribs 1022 is 10 mm.
[0072] The raw materials of the waterproof layer 103 are made of the following raw materials in parts by weight: 35 parts of linear low-density polyethylene, 35 parts of medium-density polyethylene, 35 parts of ethylene-vinyl acetate copolymer, and 3.5 parts of antioxidant 4020.
[0073] Linear low-density polyethylene, medium-density polyethylene, ethylene-vinyl acetate copolymer and antioxidant 4020 are put into an open mill for mixing at a temperature of 70°C and a drilling speed of 50 rpm. The evenly mixed rubber material is put into an extruder at a temperature of 110°C and extruded into a continuous sheet to obtain a waterproof layer 103.
[0074] The raw materials of the wear-resistant layer 104 are made of the following raw materials in parts by weight: 70 parts of natural rubber, 30 parts of butadiene rubber, 35 parts of carbon black, 7.5 parts of white carbon black, 10 parts of aromatic oil, 2 parts of antioxidant 4020, 23 parts of sulfur, and 1.5 parts of aluminum oxide.
[0075] Natural rubber, butadiene rubber, carbon black, white carbon black, aromatic oil, antioxidant 4020, sulfur and alumina are put into an open mill for mixing at a temperature of 70°C and a drilling speed of 50 rpm. The uniformly mixed rubber material is put into an extruder at a temperature of 110°C and extruded into a continuous sheet to obtain a wear-resistant layer 104.
[0076] Example 3
[0077] The bonding layer 101 is made of a composite bonding agent, and the composite bonding agent is prepared from the following raw materials in parts by weight: 100 parts of butyl rubber, 50 parts of calcium carbonate powder, 7 parts of cyclohexane oil, 30 parts of polyisobutylene, 10 parts of APAO, and 6 parts of aluminum oxide powder.
[0078] The butyl rubber, calcium carbonate powder, cyclohexane oil, polyisobutylene, APAO and alumina powder are put into an open mill for mixing at a temperature of 70°C and a drilling speed of 50 rpm. The uniformly mixed rubber material is put into an extruder at a temperature of 110°C and extruded into a continuous sheet to obtain a bonding layer 101.
[0079] The raw materials of the shock-absorbing and energy-absorbing layer 102 are made of the following raw materials in parts by weight: 100 parts of natural rubber, 50 parts of carbon black, 2 parts of microcrystalline wax, 1 part of sulfur, 3 parts of antioxidant RD, 1.5 parts of antioxidant 4020, 0.8 parts of accelerator CZ, and 0.8 parts of accelerator DM.
[0080] The above-mentioned natural rubber, carbon black, microcrystalline wax, sulfur, antioxidant RD, antioxidant 4020, accelerator CZ and accelerator DM are put into an open mill for mixing at a temperature of 70°C and a drilling speed of 50rpm. The uniformly mixed rubber material is put into an extruder at a temperature of 110°C, and the rubber material is extruded into strips, and then cut into blocks in batches using a rubber cutting machine. The block rubber material is heated to 65°C and placed in a molding mold, and hydraulic pressure molding is performed to obtain a shock-absorbing and energy-absorbing layer.
[0081] The thickness of the bottom plate 1021 is 10 mm, the height of the ribs 1022 is 50 mm, the width of the upper part of the ribs is 30 mm, the width of the lower part of the ribs is 50 mm, and the interval between two adjacent ribs 1022 is 10 mm.
[0082] The raw materials of the waterproof layer 103 are made of the following raw materials in parts by weight: 40 parts of linear low-density polyethylene, 40 parts of medium-density polyethylene, 40 parts of ethylene-vinyl acetate copolymer, and 0.5 parts of antioxidant 4020.
[0083] Linear low-density polyethylene, medium-density polyethylene, ethylene-vinyl acetate copolymer and antioxidant 4020 are put into an open mill for mixing at a temperature of 70°C and a drilling speed of 50 rpm. The evenly mixed rubber material is put into an extruder at a temperature of 110°C and extruded into a continuous sheet to obtain a waterproof layer 103.
[0084] The raw materials of the wear-resistant layer 104 are made of the following raw materials in parts by weight: 70 parts of natural rubber, 30 parts of butadiene rubber, 50 parts of carbon black, 10 parts of white carbon black, 10 parts of aromatic oil, 3 parts of antioxidant 4020, 4 parts of sulfur, and 2 parts of aluminum oxide.
[0085] Natural rubber, butadiene rubber, carbon black, white carbon black, aromatic oil, antioxidant 4020, sulfur and alumina are put into an open mill for mixing at a temperature of 70°C and a drilling speed of 50 rpm. The uniformly mixed rubber material is put into an extruder at a temperature of 110°C and extruded into a continuous sheet to obtain a wear-resistant layer 104.
[0086] Example 4
[0087] The bonding layer 101 is made of a composite bonding agent, and the composite bonding agent is prepared from the following raw materials in parts by weight: 100 parts of butyl rubber, 50 parts of calcium carbonate powder, 7 parts of cyclohexane oil, 30 parts of polyisobutylene, 10 parts of APAO, and 6 parts of aluminum oxide powder.
[0088] The butyl rubber, calcium carbonate powder, cyclohexane oil, polyisobutylene, APAO and alumina powder are put into an open mill for mixing at a temperature of 70°C and a drilling speed of 50 rpm. The uniformly mixed rubber material is put into an extruder at a temperature of 110°C and extruded into a continuous sheet to obtain a bonding layer 101.
[0089] The raw materials of the shock-absorbing and energy-absorbing layer 102 are made of the following raw materials in parts by weight: 100 parts of natural rubber, 50 parts of carbon black, 2 parts of microcrystalline wax, 1 part of sulfur, 3 parts of antioxidant RD, 1.5 parts of antioxidant 4020, 1.2 parts of accelerator CZ, and 0.8 parts of accelerator DM.
[0090] The above-mentioned natural rubber, carbon black, microcrystalline wax, sulfur, antioxidant RD, antioxidant 4020, accelerator CZ and accelerator DM are put into an open mill for mixing at a temperature of 70°C and a drilling speed of 50rpm. The uniformly mixed rubber material is put into an extruder at a temperature of 110°C, and the rubber material is extruded into strips, and then cut into blocks in batches using a rubber cutting machine. The block rubber material is heated to 65°C and placed in a molding mold, and hydraulic pressure molding is performed to obtain a shock-absorbing and energy-absorbing layer.
[0091] Wherein: the thickness a of the bottom plate 1021 is 20 mm, the height b of the rib 1022 is 40 mm, the width c of the upper part of the rib is 40 mm, the width of the lower part of the rib is 50 mm, and the interval d between two adjacent ribs 1022 is 5 mm.
[0092] The raw materials of the waterproof layer 103 are made of the following raw materials in parts by weight: 40 parts of linear low-density polyethylene, 40 parts of medium-density polyethylene, 40 parts of ethylene-vinyl acetate copolymer, and 5 parts of antioxidant 4020.
[0093] Linear low-density polyethylene, medium-density polyethylene, ethylene-vinyl acetate copolymer and antioxidant 4020 are put into an open mill for mixing at a temperature of 70°C and a drilling speed of 50 rpm. The evenly mixed rubber material is put into an extruder at a temperature of 110°C and extruded into a continuous sheet to obtain a waterproof layer 103.
[0094] The raw materials of the wear-resistant layer 104 are made of the following raw materials in parts by weight: 70 parts of natural rubber, 30 parts of butadiene rubber, 50 parts of carbon black, 10 parts of white carbon black, 10 parts of aromatic oil, 3 parts of antioxidant 4020, 4 parts of sulfur, and 2 parts of aluminum oxide.
[0095] Natural rubber, butadiene rubber, carbon black, white carbon black, aromatic oil, antioxidant 4020, sulfur and alumina are put into an open mill for mixing at a temperature of 70°C and a drilling speed of 50 rpm. The uniformly mixed rubber material is put into an extruder at a temperature of 110°C and extruded into a continuous sheet to obtain a wear-resistant layer 104.
[0096] Comparative Example 1
[0097] This example uses a common EVA waterproof board, and its raw materials are made of the following raw materials in parts by weight: 35 parts of linear low-density polyethylene, 35 parts of medium-density polyethylene, 35 parts of ethylene-vinyl acetate copolymer, and 3 parts of antioxidant 4020.
[0098] The above-mentioned linear low-density polyethylene, medium-density polyethylene, ethylene-vinyl acetate copolymer and antioxidant 4020 are put into an open mill for mixing at a temperature of 70°C and a drilling speed of 50rpm. The evenly mixed rubber material is put into an extruder at a temperature of 110°C and extruded into a continuous sheet to obtain the waterproof board.
[0099] Comparative Example 2
[0100] The comparative example uses a combination of EVA waterproof board and non-woven geotextile commonly used in tunnels. The raw materials of the EVA waterproof board are made of the following raw materials in parts by weight: 35 parts of linear low-density polyethylene, 35 parts of medium-density polyethylene, 35 parts of ethylene-vinyl acetate copolymer, and 3 parts of antioxidant 4020.
[0101] The above-mentioned linear low-density polyethylene, medium-density polyethylene, ethylene-vinyl acetate copolymer and antioxidant 4020 are put into an open mill for mixing at a temperature of 70°C and a drilling speed of 50rpm. The evenly mixed rubber material is put into an extruder at a temperature of 110°C and extruded into a continuous sheet to obtain the waterproof board.
[0102] Apply 406 instant adhesive to the upper and lower surfaces of the waterproof board, and cover the upper and lower surfaces of the waterproof board with non-woven fabric to obtain an EVA waterproof board and non-woven fabric combination material.
[0103] The dynamic ratio, fatigue resistance, and static modulus change rate after hot air aging of the rubber composite materials for tunnel waterproofing and shock absorption obtained in the above examples and comparative examples were tested, and the results are listed in Table 1.
[0104] Among them, dynamic magnification: tested in accordance with Appendix B of GB / T 39705-2020 "Vibration Isolation Pads for Rail Transit Roadbeds";
[0105] Fatigue resistance: Tested in accordance with Appendix C of GB / T 39705-2020 "Vibration Isolation Pads for Rail Transit Roadbeds";
[0106] Wear resistance: The wear test shall be carried out in accordance with the provisions of Chapter 9 of GB / T 42122-2022 Determination of wear resistance of vulcanized rubber or thermoplastic rubber, i.e. the improved Lamborn abrasion tester method, and the volume loss per unit stroke shall be used as the wear performance index.
[0107] Table 1 Performance test results of rubber composite materials for tunnel waterproofing and shock absorption
[0108]
[0109] It can be concluded from Table 1 that the dynamic multiple of the rubber composite material for tunnel waterproofing and shock absorption prepared by the present invention is less than 1.21, the thickness change rate is less than or equal to 2.3% after 30 million times of dynamic fatigue, the static modulus change rate is less than or equal to 4.0%, there is no obvious crack in appearance, and the wear resistance is good, and the volume loss per unit stroke is less than or equal to 0.28, indicating that the composite rubber material has excellent wear resistance and aging resistance compared with the traditional tunnel seismic isolation layer, and can flexibly adapt to seismic loads.
Claims
1. A rubber composite material for tunnel waterproofing and shock absorption, characterized in that: From top to bottom, it comprises a wear-resistant layer (104), a waterproof layer (103), a shock-absorbing and energy-absorbing layer (102) and a bonding layer (101) which are stacked together in sequence; The bonding layer (101) is made of a composite bonding agent; The shock-absorbing and energy-absorbing layer (102) comprises a bottom plate (1021), on which a plurality of ribs (1022) are arranged, each of the ribs (1022) is arranged along a front-to-back direction, and a plurality of the ribs (1022) are arranged at intervals along a left-to-right direction, each of the ribs (1022) is wide at the bottom and narrow at the top, and its longitudinal section is a trapezoid that is wide at the bottom and narrow at the top; the ribs (1022) are used to reduce the energy transmitted to the tunnel by an earthquake.
2. The rubber composite material for tunnel waterproofing and shock absorption according to claim 1, characterized in that: The thickness of the bottom plate (1021) is 10 to 20 mm, the height of the ribs (1022) is 40 to 50 mm, the upper width of the ribs (1022) is 30 to 40 cm, the lower width is 50 cm, and the interval between two adjacent ribs (1022) is 5 to 10 mm.
3. The rubber composite material for tunnel waterproofing and shock absorption according to claim 2, characterized in that: The composite adhesive is prepared from the following raw materials in parts by weight: 100 parts of butyl rubber, 30-50 parts of calcium carbonate powder, 3-7 parts of cyclohexane oil, 10-30 parts of polyisobutylene, 5-10 parts of APAO, and 2-6 parts of aluminum oxide powder.
4. The rubber composite material for tunnel waterproofing and shock absorption according to claim 3, characterized in that: The raw materials of the shock-absorbing and energy-absorbing layer (102) are made of the following raw materials in parts by weight: 100 parts of natural rubber, 50 parts of carbon black, 2 parts of microcrystalline wax, 1 part of sulfur, 1-3 parts of antioxidant RD, 0.5-1.5 parts of antioxidant 4020, 0.8-1.2 parts of accelerator CZ, and 0.5-0.8 parts of accelerator DM.
5. The rubber composite material for tunnel waterproofing and shock absorption according to claim 4, characterized in that: The raw materials of the waterproof layer (103) are made of the following raw materials in parts by weight: 30-40 parts of linear low-density polyethylene, 30-40 parts of medium-density polyethylene, 30-40 parts of ethylene-vinyl acetate copolymer, and 2-5 parts of antioxidant 4020.
6. The rubber composite material for tunnel waterproofing and shock absorption according to claim 5, characterized in that: The raw materials of the wear-resistant layer (104) are made of the following raw materials in parts by weight: 70 parts of natural rubber, 30 parts of butadiene rubber, 20-50 parts of carbon black, 5-10 parts of white carbon black, 10 parts of aromatic oil, 1-3 parts of antioxidant 4020, 2-4 parts of sulfur, and 1-2 parts of aluminum oxide.
7. The rubber composite material for tunnel waterproofing and shock absorption according to claim 6, characterized in that: The thickness of the bonding layer (101) is 1 mm; The thickness of the shock-absorbing and energy-absorbing layer (102) is 60 mm; The thickness of the waterproof layer (103) is 1.2 mm; The thickness of the wear-resistant layer (104) is 0.5 mm.
8. A method for preparing a rubber composite material for tunnel waterproofing and shock absorption according to any one of claims 1 to 7, characterized in that: These include: Step 1, weigh the above raw materials; Step 2: Put butyl rubber, calcium carbonate powder, cyclohexane oil, polyisobutylene, APAO and alumina powder into an open mill for mixing at a temperature of 40-85° C. and a drilling speed of 30-60 rpm, put the mixed rubber into an extruder at a temperature of 100-125° C., extrude into a continuous sheet, and obtain a bonding layer (101); Put natural rubber, carbon black, microcrystalline wax, sulfur, antioxidant RD, antioxidant 4020, accelerator CZ, and accelerator DM into an open mill for mixing at a temperature of 40-85° C. and a drilling speed of 30-60 rpm, put the mixed rubber material into an extruder at a temperature of 90-120° C., extrude the rubber material into strips, and then cut it into blocks, heat the block rubber material to 50-70° C. and place it in a molding mold, and perform hydraulic pressure molding to obtain a shock-absorbing and energy-absorbing layer (102); Putting linear low-density polyethylene, medium-density polyethylene, ethylene-vinyl acetate copolymer and antioxidant 4020 into an open mill for mixing at a temperature of 40-85° C. and a drilling speed of 30-60 rpm, putting the mixed rubber material into an extruder at a temperature of 100-125° C. and extruding it into a continuous sheet to obtain a waterproof layer (101); Put natural rubber, butadiene rubber, carbon black, white carbon black, aromatic oil, antioxidant 4020, sulfur and alumina into an open mill for mixing at a temperature of 40-85° C. and a drilling speed of 30-60 rpm, put the mixed rubber material into an extruder at a temperature of 100-125° C., extrude it into a continuous sheet, and obtain a wear-resistant layer (104); Step 3: stack the wear-resistant layer (104), waterproof layer (103), shock-absorbing layer (102) and adhesive layer (101) in order from top to bottom, heat to 100-120° C., perform hot pressing for 10-20 seconds, and cool to obtain the product.